Utilization of Information and Communication Technology in Learning by Elementary School Teachers - Lilis Badriah; Eigis Yani Pramularso (Universitas Muhammadiyah Mataram, 2021)
This research aims to know the utilization of information and communication technology of teachers in learning planning, learning process, and evaluation of learning at SDIT Nurul Fikri Depok. This type of research uses surveys with quantitative and qualitative descriptive data analysis. Sampling techniques use simple random sampling regardless of population level. Data retrieval techniques by giving questionnaires to teachers SDIT Nurul Fikri a number of 32 people. The results showed that the utilization of information and communication technology in learning planning is very high with a percentage of 86.63%, the utilization of information and communication technology in the learning process is very high with a percentage of 81.88%, the utilization of information and communication technology in the evaluation of learning is very high with a percentage of 86.67%. Overall the utilization of information and communication technology in learning by class teachers at SDIT Nurul Fikri is very high with a percentage of 85.06%.